2014
DOI: 10.1186/1471-2407-14-100
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous expression of flotillin-1, flotillin-2, stomatin and caveolin-1 in non-small cell lung cancer and soft tissue sarcomas

Abstract: BackgroundAt the present time, there is a lack of data about the involvement of flotillins and stomatin in the development of non-small cell lung cancer (NSCLC) and soft tissue sarcomas (STS). Moreover, changes in expression of members of different families of the microdomain-forming proteins (caveolins and SPFH-domain containing family) are usually investigated independently of each other. In this study we performed a combined analysis of flotillins, stomatin, and caveolin-1 expression in these pathologies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
3
17
1
Order By: Relevance
“…Moreover, we provided the first demonstration of this correlation also in RMS, a sarcoma of skeletal muscle origin. The only previous study on sarcomas revealed increased FLOT1 mRNA expression in synovial sarcoma, fibrous histiocytoma and malignant schwannoma (Arkhipova et al, 2014). Using RMS cell lines, we demonstrated higher flotillin-1 and -2 expression in the cell lines derived from ARMS (the most invasive type) than in those derived from ERMS.…”
Section: Discussionmentioning
confidence: 46%
“…Moreover, we provided the first demonstration of this correlation also in RMS, a sarcoma of skeletal muscle origin. The only previous study on sarcomas revealed increased FLOT1 mRNA expression in synovial sarcoma, fibrous histiocytoma and malignant schwannoma (Arkhipova et al, 2014). Using RMS cell lines, we demonstrated higher flotillin-1 and -2 expression in the cell lines derived from ARMS (the most invasive type) than in those derived from ERMS.…”
Section: Discussionmentioning
confidence: 46%
“…Arkhipova’s and colleagues recently reported that down-regulation of stomatin mRNA was correlated with positive lymph node status in 48 patients [19]. In our study, we initially proposed that lipid-raft localized stomatin might be able to modulate the activity of the HER2-positive breast cancer.…”
Section: Discussionmentioning
confidence: 72%
“…Recently reported by Arkhipova and colleagues in 2014, stomatin is down-regulated in non-small cell lung cancer and is associated with lymph node metastases [19]. This is the first and the only one study to demonstrate that stomatin has a role in carcinogenesis.…”
Section: Introductionmentioning
confidence: 82%
“…As shown in Fig. 2, [17][18][19][20][21][22][23][24][25][26][27][28][29] various molecules involved in disease progression have also been found to be associated with lipid rafts and caveolae.…”
Section: Micrornas As Modulators Of Lipid Rafts In Human Diseasesmentioning
confidence: 93%